MASS SPECTROMETRY OF RNA: LINKING THE GENOME TO THE PROTEOME - Meng, Zhaojing (2006)
Ribonucleic acids (RNAs) are continuing to attract increased attention as they are found to play pivotal roles in biological system. Just as genomics and proteomics have been enabled by the development of effective analytical techniques and instrumentation, the large-scale analysis of non-protein coding (nc)RNAs will benefit as new analytical methodologies are developed which are appropriate to RNA analysis. Mass spectrometry offers a number of advantageous for RNA analysis arising from its ability to provide mass and sequence information starting with limited amounts of sample. This Briefings will highlight recent developments in the field that enable the characterization of RNA modification status, RNA tertiary structures, and ncRNA expression levels. These developments will also be placed in perspective of how mass spectrometry of RNAs can help elucidate the link between the genome and proteome.